Metabolic tumor volume by positron emission tomography/computed tomography as a clinical parameter to determine therapeutic modality for early stage Hodgkin's lymphoma. Issue 12 (23rd October 2013) - Song, Moo‐Kon; Chung, Joo‐Seop; Lee, Je‐Jung; Jeong, Shin Young; Lee, Sang‐Min; Hong, Jun‐Shik; Chong, Ari; Moon, Joon‐Ho; Kim, Ji‐Hyun; Lee, Seok‐Mo; Kim, Seong Jang; Shin, Ho‐Jin
<x xml:space="preserve">Abstract</x> Recent studies have shown that metabolic tumor volume (MTV) by positron emission tomography/computed tomography (PET/CT) is an important prognostic parameter in patients with non‐Hodgkin's lymphoma. However, it is unknown whether doxorubicin, bleomycin, vinblastine, dacarbazine (ABVD) alone in early stage Hodgkin's lymphoma would lead to similar disease control as combined modality therapy (CMT) using MTV by PET/CT. One hundred and twenty‐seven patients with early stage Hodgkin's lymphoma who underwent PET/CT at diagnosis were enrolled. The MTV was delineated on PET/CT by the area ≥SUVmax, 2.5 (standardized uptake value [SUV]). Sixty‐six patients received six cycles of ABVD only. The other 61 patients received CMT (involved‐field radiotherapy after 4–6 cycles of ABVD). The calculated MTV cut‐off value was 198 cm3. Clinical outcomes were compared according to several prognostic factors (i.e. age ≥50 years, male, performance status ≥2, stage II, B symptoms, ≥4 involved sites, extranodal site, large mediastinal mass, CMT, elevated erythrocyte sedimentation rate and high MTV). Older age (progression‐free survival [PFS], P = 0.003; overall survival [OS], P = 0.007), B symptoms (PFS, P = 0.006; OS, P = 0.036) and high MTV (PFS, P = 0.008; OS, P = 0.007) were significant independent prognostic factors. Survival of two high MTV groups treated with ABVD only and CMT were lower than the low MTV groups (PFS, P < 0.012; OS, P < 0.045). ABVD alone was sufficient to control disease in those with low MTV status. However, survival was poor, even if the CMT was assigned a high MTV status. The MTV would be helpful for deciding the therapeutic modality in patients with early stage Hodgkin's lymphoma.